Analysis on adulthood weight change in adults in China - Zhou, M; Zhu, N; Yu, C; Du, H; Lyu, J; Guo, Y; Bian, Z; Tan, Y; Pei, P; Chen, J; Chen, Z; Li, L; et al. (Chinese Medical Association, 2019)
Objective: To understand the characteristics of adulthood weight change through the analysis on data from China Kadoorie Biobank (CKB) Study of 0.5 million adults from ten areas in China. Methods: An electronic questionnaire was used to collect the information about the body weight at age 25 years, social-demographic characteristics and lifestyle of the study subjects and their body weight were measured. After excluding the adults with self-reported histories of coronary heart disease, stroke, cancer or diabetes and those who had no data of body weight at age 25 years and those aged outside of 35-70 years, a total of 360 903 adults were included in the analysis. Adulthood weight change were defined as difference value between current body weight and body weight at age 25 years. Results: The mean adulthood weight change of the participants was 4.9 kg. The adults living in urban area showed more body weight increase compared with those living in rural area, so did the adults in northern area compared with those in southern area. Among the ten areas in China, Qingdao reported the highest adulthood weight increase (9.3 kg), and Gansu reported the lowest adulthood weight increase (1.5 kg). Older adults had higher BMI at early adulthood (25 years old), but the adults aged 45-50 years had the highest adulthood body weight increase. Adults with higher educational level, higher household income level, but lower physical activity level had more body weight increase, while current smokers, farmers and workers had less body weight increase. BMI at age 25 years was negatively associated with adulthood body weight change, but current BMI was positively associated with adulthood body weight change (P<0.001). Conclusion: Adulthood body weight change varied greatly among population with different demographic characteristics and lifestyle and in ten areas in China.